2016
DOI: 10.1155/2016/2604980
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of High-Resolution Satellite-Based Real-Time and Post-Real-Time Precipitation Estimates during 2010 Extreme Flood Event in Swat River Basin, Hindukush Region

Abstract: Satellite-based real-time and post-real-time precipitation estimates of Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA-3B42) were evaluated during an extreme heavy precipitation event (on 28–30 July 2010) over Swat River Basin and adjacent areas in Hindukush Region. Observations of 15 rain gauging stations were used for the evaluation of TMPA products. Results showed that the spatial pattern of precipitation in the event was generally captured by post-real-time product (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…Several studies have been carried out to develop and evaluate these products in Pakistan [37][38][39][40][41] and all over the world. However, the supremacy of any specific product has not been observed in different regions with diverse climatic conditions [31,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been carried out to develop and evaluate these products in Pakistan [37][38][39][40][41] and all over the world. However, the supremacy of any specific product has not been observed in different regions with diverse climatic conditions [31,42].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used products include the Climate Prediction Center morphing technique (CMORPH) [1], the European Organization for the Exploitation of Meteorological Satellites (EUMETSAT)'s Multi-sensor Precipitation Estimate (MPE) [2], the European Centre for Medium-Range Weather Forecasts (ECMWF)'s Era-Interim product [3], the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN), the PERSIANN Cloud Classification System estimation (PERSIANN-CCS) [4], the Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis products (TMPA) versions 6 (3B42-V6) and 7 (3B42-V7) [5,6] and the Integrated Multi-Satellite Retrievals for Global Precipitation Measurement (IMERG) product [7]. Numerous studies have been made to evaluate the performance of these precipitation satellite products on the regional and global scale (e.g., Asia [8][9][10][11], North and Central America [12][13][14][15][16], South America [17][18][19][20], Europe [21][22][23][24], Australia [25][26][27][28], Oceans [29,30], other [31][32][33][34][35][36] and in Pakistan [37][38][39][40][41]...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that 3B42V7 showed superiorities over 3B42V6 and 3B42RT, it still exhibits poor agreements with the gauge-based reference data at daily and seasonal time scales as analyzed with lower values of CC. To date, the daily and seasonal precipitation estimates derived from 3B42V7 were found to have poor correlation with the reference data in Hindukush Mountainous range [15,19], Tanzania [9], Malaysia [34], Taiwan, the U.S. Rocky Mountains and Nepal [20]. In contrast, a good correlation was found in China [28], Turkey [20], and Morocco [13].…”
Section: Accuracy Of Tmpa Products At Different Precipitation Intensimentioning
confidence: 92%
“…Although some studies have also documented the performance of 3B42V7 in different regions of the world [14][15][16][17][18], limited studies have reported on its performance relative to its predecessor (3B42V6) and near real time product (3B42RT) in complex terrain regions having cryospheric environment. Thus, a river basin situated in the high mountains of Hindukush-Karakoram-Himalayan (HKH) region [15,19] has been chosen for undertaking a comprehensive and comparative assessment of TMPA products with a wide variety of statistical indicators.…”
Section: Introductionmentioning
confidence: 99%